O-026 Does Transfer Status Affect Outcomes in Acute Ischaemic Stroke Patients Treated Endovascularly?. (14th July 2013) - Soltanolkotabi, M; Shaibani, A; Hurley, M; Prabhakaran, S; Lee, V; Conners, J; Ansari, S
Abstract : Background: Access to intra-arterial therapy (IAT) for acute ischaemic stroke (AIS) is limited to comprehensive stroke centres (CSCs) with timely access deemed critical for success. Inter-hospital transfers represent a growing subset of patients in which outcomes have not been well-studied. Design/Methods: We retrospectively analysed consecutive anterior circulation AIS patients that underwent IAT at 4 institutions from2006–2011. We excluded patients selected using perfusion imaging. Patient demographics, medical risk factors, presentations, technical, and clinical (NIHSS and mRS scores) outcomes, complications, and mortality were studied. Symptom-onset, groin puncture, and end-of-procedure times were recorded. THRIVE scores were calculated. Successful recanalisation was defined as TIC I≥2b. Good functional outcome was defined as mRS 0–2 at 90 days. Patients were categorised into those who were transferred from outside institutions and those who presented directly to the CSCs. Results: 116 patients were studied. 68 (58.6%) were transferred from outside institutions. Transfers and non-transfers were similar in THRIVE scores (p=0.300), median symptom-onset to groin puncture times (306 vs 315 minutes; p=0.572), successful recanalisation (p=0.574), and symptomatic IC H (13.2 vs 10.4, p=0.776), but differed by age (59 vs 69 years; p=0.002), prior stroke (3% vs 22%, p=0.002), cardiac history (17.9 vs 36.6%, p=0.040), baseline NIHSS (20 vs 17, p=0.005), and location of occlusion (45.6% vs 22.9% IC A, p=0.012). Transfer patients had significantly worse outcomes at 90 days (mRS 0–2: 16.2% vs 60.4%, p>0.001). In multivariate analysis, transfer status was an independent predictor of poor functional outcome (adj. OR 0.05, 0.011 0.222), adjusting for relevant covariates. Conclusions: Transferred AIS patients have worse functional outcomes at 90 days than non-transfers, independent of baseline risk factors, stroke severity, time to IAT, and procedural success/complications. Further investigation should focus on residual factors that may contribute to our findings such as baseline/final infarct volumes, pre-morbid functional status, and post-stroke care. Disclosures: M. Soltanolkotabi: None. A. Shaibani: None. M. Hurley: None. S. Prabhakaran: None. V. Lee: None. J. Conners: None. S. Ansari: None.